Vigour assessment in Pinus radiata D. Don seeds : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in seed technology at Massey University, Palmerston North, New Zealand - Kartiko, Hero Dien P. (Hero Dien Pancang) (Massey University, 1990)
The sensitivity and/or predictivity of various vigour test methods (which include conductivity, tetrazolium, x-ray contrast, seedling growth, controlled deterioration, complex stressing vigour, and low temperature/osmotic stress tests) for prepared lots of Pinus radiata seeds were investigated in this study. The best tests were the controlled deterioration test with two days aging treatment (CD2d) test), the prechilled seedling growth test (SG+pr test), and the complex stressing vigour test (CSV test). These were then further investigated to evaluate their ability to predict the performance of different seed lots at the Forest Research Institute (FRI) nursery, Rotorua. The CD2d, SG + pr and CSV tests showed good correlation, especially with percentage of plan table seedlings at the FRI nursery. In addition, these tests seem to have met most of the AOSA's (1983) criteria for a practical vigour testing, as they are simple and can be done in a relatively short period of time. For application purposes, it is suggested that the test parameters which gave the highest correlation coefficient value with percentage of plan table seedlings in the nursery should be used as a reliable measurement. Therefore, percentage normal seedlings should be used in either the CD2d or the CSV test, whereas T50 radicle emergence seems more predictive in the SG+pr test. For application in other nurseries, these tests may still be valid, especially if pre-sowing treatment and nursery conditions are about the same as in the FRI nursery. If conditions do differ, however, the CD2d and SG + pr tests are more likely to be useful than the CSV test. This hypothesis is based on the fact that the CD2d and SG + pr tests also gave good correlations with the glasshouse (optimum conditions) and winter field tests (sub-optimum conditions). In contrast, there was no significant correlation given by the CSV test in relation to the glasshouse and winter field tests. Seed weight had a significant effect on seedling dry weight and Tso radicle emergence if there was a large seed weight variation between seed lots. In this case, generally heavier seeds had better performance than the lighter ones. If there was only small variation in overall seed weight among seed lots, however, the important effects of individual differences in seed weights were masked. The direction of further studies would seem to be to evaluate the reproducibility of correlation coefficient values and regression equations by the CD2d, SG + pr and CSV tests in the same nursery site over several sowings. Additionally, vigour test evaluation using seed lots from individual clones would also seem to be important.
Keywords: Pinus radiata; Seeds; Quality; Viability